(3SjQI GdSjO CMeO GdHOhis
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdLfI OGQ GdeJbjf hLYd GdfGQ eKhi GdcGaQjf hCScf GdEjeGf ai bdhH GdYGQajf s
(3BNQgG (B:s
(3hbO TgO HUMI gPg GdfSHI GdTQjaI GdbGVi YHO GdhgGH Hf GdfejdI hfSNJ efg ddTQja GdMSjf GdMGce HeOjfI GdQShd HOGQ GdQUGU Ydi SGcfgG CaVd GdUdGI hGdSdGe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs